Do Audits Deter or Provoke Future Tax Noncompliance? Evidence on Self-Employed Taxpayers. (9th January 2020) - Beer, Sebastian; Kasper, Matthias; Kirchler, Erich; Erard, Brian
Abstract: This article employs unique tax administrative data and operational audit information, including risk scores used for audit selection, from a sample of approximately 7500 self-employed US taxpayers to investigate the effects of operational tax audits on future reporting behavior. Our estimates indicate that audits can have substantial deterrent or counter-deterrent effects, depending on the audit outcome. In the aggregate, taxable income is estimated to increase by roughly 15% 1 year after an operational audit. However, this figure masks substantial heterogeneity within the population. Among those taxpayers who receive an additional tax assessment, reported taxable income is estimated to be 64% higher in the first year after the audit (44% after 3 years) than it would have been in the absence of the audit. In contrast, among those taxpayers who do not receive an additional tax assessment, reported taxable income is estimated to be approximately 15% lower the year after the audit (21% 3 years later) than it would have been had the audit not taken place. Our results suggest that improved targeting of audits toward noncompliant taxpayers would not only yield more direct audit revenue but also pay dividends in terms of future tax collections.